2016
DOI: 10.1103/physreva.94.013830
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear fiber gyroscope for quantum metrology

Abstract: We examine the performance of a nonlinear fiber gyroscope for improved signal detection beating the quantum limits of its linear counterparts. The performance is examined when the nonlinear gyroscope is illuminated by practical field states, such as coherent and quadrature squeezed states. This is compared with the case of more ideal probes such as photon-number states.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Since the generators for linear and nonlinear phase accumulation are quite different, the corresponding optimized input states make huge differences. Recent interest has moved to examine the role of nonlinear interaction in the phase accumulation [34,[44][45][46], which requires different optimization strategies. However, due to the difficulties of preparing optimal input entangled states and manipulating the nonlinear phase accumulation, the experimental demonstrations of parameter estimation with nonlinear phase accumulation are still rare [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Since the generators for linear and nonlinear phase accumulation are quite different, the corresponding optimized input states make huge differences. Recent interest has moved to examine the role of nonlinear interaction in the phase accumulation [34,[44][45][46], which requires different optimization strategies. However, due to the difficulties of preparing optimal input entangled states and manipulating the nonlinear phase accumulation, the experimental demonstrations of parameter estimation with nonlinear phase accumulation are still rare [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this idea, many schemes of quantum gyroscopes have been proposed. It was found that the entanglement in N00N states [29,30], continuous-variable squeezing [31][32][33], and optical nonlinearity [34] can enhance the sensitivity of optical gyroscopes beyond the SNL. A quantumenhanced sensitivity can also be achieved in matter-wave gyroscopes [35][36][37][38] by using spin squeezing [39][40][41] or entanglement.…”
mentioning
confidence: 99%